Praktik Nepotisme pada Pemerintahan Desa (Jurnal Sosial Humaniora dan Pendidikan, 2025)
Nepotism in village governance is a phenomenon that negatively impacts government administration, public services, and rural development. This study aims to analyze the practice of nepotism in village governance through the lens of critical sociology, particularly within the theoretical frameworks of Michel Foucault and Karl Marx. Using a literature review approach, this research identifies that nepotism in village governance is often legitimized through patronage culture and kinship ties, which hinder meritocracy and create social inequality. The findings reveal that nepotistic practices lead to weak transparency, poor public service delivery, and increasing public distrust in village governance. From Foucault’s perspective, nepotism is part of a power mechanism that sustains the dominance of certain groups, while Marx highlights nepotism’s role in maintaining social and economic stratification. Therefore, reforms in the recruitment system for village officials, enhanced transparency, and the implementation of meritocracy-based governance principles are necessary to mitigate the negative impacts of nepotism in village governance.